Integrating Social Sciences and Technology in Islamic Religious Education for Moral Development - Bahri, Saiful; Mudarris, Badrul (Universitas Nurul Jadid Probolinggo, Indonesia, 2024)
This research investigates the integration of multidisciplinary approaches in Islamic Religious Education (PAI) to enhance character development among students in contemporary educational settings. As modern education systems face increasing pressure to adapt to technological advancements and global challenges, religious education must evolve to remain relevant. The study explores how combining traditional religious teachings with insights from social sciences, psychology, and technology can create a more comprehensive and effective framework for character building. Previous research on interdisciplinary approaches in education has highlighted their potential to enrich curricula and foster deeper engagement with students, but little has been done to examine this integration within Islamic Religious Education. Using qualitative methods, including interviews, observations, and document analysis, this study examines the application of a multidisciplinary approach in PAI at MA Probolinggo, a religious school in Indonesia. The findings reveal that integrating disciplines such as social sciences and technology not only makes religious teachings more applicable to students’ daily lives but also increases their engagement and moral understanding. This integration enhances the relevance of PAI and supports the development of students’ ethical and social awareness. These findings suggest that educators should consider adopting multidisciplinary methods in PAI to better prepare students for the complexities of modern life. The study contributes to the growing body of research on innovative approaches in religious education and offers practical insights for curriculum development in Islamic schools.